Effect of Preoperative Antianxiety Medications on Blood Pressure and Blood Loss in Total Knee Arthroplasty: A Case-Control Study - Zuhdi O. Elifranji; Jihad M. Al-Ajlouni; Munther G. Al-Saber; Yazan S. Hammad; Basel A. Baniatta; Sara N. Alshoubaki; Mohammad S. Jabaiti; Ahmad M. Alkhatib; Abdelrahman M. Abu awad; Abdelrahman E. Altarazi; Aseel N. Abdin; Abdallah Al-Ani; et al. (Advances in Orthopedics)
Background. The increasing number of canceled operations in patients undergoing total knee arthroplasty (TKA) due to high blood pressure readings has put a considerable burden on surgeons. In this study, we aim to assess the effect of giving antianxiety drugs preoperatively on maintaining blood pressure (BP) and blood loss for patients undergoing TKA surgery. Methods. This retrospective case-control study included patients who underwent total knee arthroplasty and divided them into two main groups: those who had taken a 3 mg bromazepam oral tablet at the night preoperatively and the control group. The blood pressure of patients was then measured preoperatively (baseline), in the morning of surgery, in the operating room before anesthesia, and during the surgery. The percentage of measured BP was calculated by dividing the measured BP by the baseline, then multiplying by 100. Results. 301 patients were included in our study: 137 received bromazepam and 164 as a control group. The ratio of systolic BP (SBP) in the morning of surgery to the baseline (percentage of morning SBP) decreased significantly in the bromazepam group compared with the controls. The ratio of SBP, in the operating room before anesthesia (percentage of preanesthesia SBP) also decreased significantly in the bromazepam group. However, the percentage of SBP in the middle of surgery did not change significantly. In addition, there was a significant difference change from the baseline in diastolic BP and mean arterial BP between the two groups in the morning of surgery, inside the theatre, and in the middle of the operation. The bromazepam group also showed a significant decrease in blood loss. Conclusion. Preoperative oral antianxiety drugs (bromazepam) helps in controlling hemodynamic changes associated with anxiety, including maintaining BP in well-controlled hypertensive and healthy patients undergoing TKA, and it plays a role in decreasing the total blood loss.